Progressive tax development in the taxation system: acomparative analysis of the EU and Central Asian countries - Azamat Baimagambetov; Serik Omirbayev (Retos: Revista de Ciencias de la Administración y Economía)
The study aims to compare the experience of implementing a progressive taxation system in the EU countries with the taxation system in Central Asia to establish the prospects for reforms in this area. The following methodological methods were used: methods of generalisation to analyse theoretical materials, methods of processing statistical results, estimation of the Gini coefficient, and assessment of the progressiveness and redistributive capacity of profitability indicators using economic and mathematical modelling methods were also used. The income tax indicators of such countries as Kazakhstan, Uzbekistan, the Kyrgyz Republic, Tajikistan and Turkmenistan were assessed. The study determined that according to the data on progressiveness and redistributive capacity due to the peculiarities of tax policy implementation, Kazakhstan, the Kyrgyz Republic and Tajikistan have a pronounced progressiveness and redistributive capacity. Turkmenistan and Uzbekistan do not have such indicators. The Gini Index (coefficient), which indicates a high degree of income inequality in these countries, is also very characteristic. On the contrary, the Gini coefficient of the leading European Union countries is higher: Belgium, Denmark, France, Germany, Spain, and Germany are characterised by a high degree of fairness in the tax structure and social sphere. Thus, the need to reform the taxation system to achieve the goals of sustainable development in Central Asian countries is an urgent problem that should be addressed and accounted for at the state level.